2021
DOI: 10.31018/jans.v13i2.2615
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon stock in different land-use systems in the hilly terrain of Mizoram, Northeast India

Abstract: Soil carbon is one of the most affected variables to land-use change in tropics. The soil carbon flux plays a major role in regulating microbial activities and nutrient distribution in soil. This study aimed to evaluate the soil carbon stock in various land uses at different depths in the hilly terrain of Mizoram, Northeast India. Soil samples at 0-10 cm, 10-20 cm and 20-30 cm soil depths were collected from Rubber plantation (RP), Oil palm plantation (OPP), Teak plantation (TP), Bamboo Forest (BF), 5 years fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…The highest SOC and SOC stock were recorded in the TDDFLUS, attributed to increased litter deposition, reduced soil disturbance, and slower decomposition rate of soil organic carbon. Conversely, WBALUS exhibited the lowest SOC concentration and stock due to intensive farming methods, which cause significant soil disruption and accelerate SOC decomposition 55–57 . Sahoo et al 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest SOC and SOC stock were recorded in the TDDFLUS, attributed to increased litter deposition, reduced soil disturbance, and slower decomposition rate of soil organic carbon. Conversely, WBALUS exhibited the lowest SOC concentration and stock due to intensive farming methods, which cause significant soil disruption and accelerate SOC decomposition 55–57 . Sahoo et al 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, WBALUS exhibited the lowest SOC concentration and stock due to intensive farming methods, which cause significant soil disruption and accelerate SOC decomposition. [55][56][57] Sahoo et al 11 reported that the amount and quality of litter in various LUSs regulate the quality of organic carbon produced, shaping the soil's physico-chemical characteristics. Variations in SOC and stock were also noted across distinct soil depths.…”
Section: Soil Organic Carbon and Soil Organic Carbon Stockmentioning
confidence: 99%
“…Available phosphorus correlated negatively with organic matter and other nutrients ( Sun et al., 2013 ; Gong and Wang, 2011 ; Wang et al., 2018 ; Liu, 2017 ). Manpoong et al. (2021) study soil carbon stock in different land-use systems in the hilly terrain of Mizoram, Northeast India, think that the land use change in the mountainous region significantly affected the carbon stock in the soil.…”
Section: Introductionmentioning
confidence: 99%